2023
DOI: 10.3390/app13105966
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Technique for Optical Inspection of Color Contact Lenses

Abstract: Colored contact lenses have gained popularity in recent years. However, their production process is plagued by low efficiency, which is attributed to the complex nature of the lens color patterns. The manufacturing process involves multiple complex steps that can introduce defects or inconsistencies into the contact lenses. Moreover, manual inspection of a considerable number of contact lenses that are produced inefficiently in terms of consistency and quality by humans is prevalent. Alternatively, automatic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Kim et al [ 12 ] and Kim et al [ 19 ] discussed the defect detection in color contact lenses from the injection molding process. However, these studies focused only on classifying the presence of defects, not on measuring the deviation distance of the center point.…”
Section: Related Workmentioning
confidence: 99%
“…Kim et al [ 12 ] and Kim et al [ 19 ] discussed the defect detection in color contact lenses from the injection molding process. However, these studies focused only on classifying the presence of defects, not on measuring the deviation distance of the center point.…”
Section: Related Workmentioning
confidence: 99%
“…Despite the common finding of DL algorithms outperforming human visual inspection [89,90], this is not always the case. Some studies reported mixed and similar results [83,91] or a lower model performance compared with human inspectors [92]. This variety of results indicates a gap in fully automated inspection and a prevalence of human intervention, including cases where algorithms initiate the inspection and inspectors intervene for dubious items or items below a predefined threshold [93,94].…”
Section: Inspection Challengesmentioning
confidence: 99%